Research in sociology- Reality and prospects- - Mortada-Nfusi, Lamia (Journal of Social Sciences and Humanities, 2023)
Contemporary sociology emerged following the industrial revolution and its social changes, where sociologists asked questions about the nature of these social changes and how societies evolved. Currently, research in sociology suffers from the predominance of applied studies; fundamental studies are rare, they are not concerned with the implications applied in a specific field, and do not seek to solve a practical problem. They seek to satisfy scientific curiosity, the aim of which is the development of knowledge and the world around us. This article is a theoretical study which aims to explain the reasons for the inventory of research in sociology, indicate the reasons for the withdrawal of theoretical studies, and I will also clarify the horizons of research in this field. Today, it turned out that there is a penchant for the study of daily life and its interactions, with all its complexity. In this article, I will try to answer the following questions: - What are the major questions that led to the emergence of sociology? - What are the reality and the prospects of research in this field?